A novel 3-D structure with tunable Poisson's ratio and adjustable thermal expansion. (December 2020) - Xu, Na; Liu, Hai-Tao
Abstract：: A novel 3-D structure is proposed by adding the reinforcing rods into the original 2-D star-shaped structure to obtain more obvious negative Poisson's ratio effect. The influence of length parameter, thickness parameter, angle parameters and material combination on the effective Poisson's ratio, effective Young's modulus and effective shear modulus of the novel 3-D structure is systematically investigated using cell-based finite element modeling. Additionally, the change rule of material combination sequence and length parameter of the structure's thermal expansion is also studied. The results show that the novel 3-D structure can achieve positive, zero and negative Poisson's ratio, as well as positive, zero and negative thermal expansion when appropriate material combination is adopted. Moreover, the negative Poisson's ratio effect of the novel 3-D structure is distinctly enhanced, and the effective Young's modulus is slightly increased through comparing with other two 3-D star-shaped structures. By selecting material combinations and structural geometry parameters, metamaterials with special properties can be designed for different application fields. Highlights: A novel 3-D metamaterial is proposed by adding the reinforcing rods. The change rule of material combination sequence is also studied. The novel 3-D metamaterial can achieve positive, zero and negative Poisson's ratio.